2021
DOI: 10.1001/jamainternmed.2020.4796
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of In-Hospital Cardiac Arrest in COVID-19

Abstract: Before the outbreak of coronavirus disease 2019 (COVID-19), 25% of patients who underwent in-hospital cardiac arrest (IHCA) survived to discharge, with the initial rhythm being nonshockable in 81% of cases. 1 Despite the outbreak causing many deaths, to our knowledge, information on IHCA among this subset of patients in the US is lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
96
4
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(113 citation statements)
references
References 4 publications
11
96
4
2
Order By: Relevance
“…In our cohort, we have demonstrated rates of ROSC and 30-day survival that are numerically higher than previously published cohorts of survival after IHCA in COVID-19, but lower than recent studies of IHCA prior to COVID-19, which demonstrated rates of ROSC of 54–64% and survival of 22–28%. 8 , 9 , 10 , 19 , 20 Since early in the pandemic there has been speculation about poor outcomes from resuscitation of patients with COVID-19. 6 , 21 These concerns have been further validated by recent studies that described the clinical outcomes of IHCA in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our cohort, we have demonstrated rates of ROSC and 30-day survival that are numerically higher than previously published cohorts of survival after IHCA in COVID-19, but lower than recent studies of IHCA prior to COVID-19, which demonstrated rates of ROSC of 54–64% and survival of 22–28%. 8 , 9 , 10 , 19 , 20 Since early in the pandemic there has been speculation about poor outcomes from resuscitation of patients with COVID-19. 6 , 21 These concerns have been further validated by recent studies that described the clinical outcomes of IHCA in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Two single-centre case series, one in New York and another in Michigan, both demonstrated 100% in-hospital mortality despite high rates of return of spontaneous circulation (ROSC). 9 , 10 More recently a multicentre collaborative published a report of 400 patients admitted across 86 ICUs who suffered IHCA, with a rate of ROSC of 33.8% and 12.0% survival to hospital discharge. 11 These studies have raised questions regarding the utility of resuscitating COVID-19 patients with IHCA, particularly when balancing risks to providers.…”
Section: Introductionmentioning
confidence: 99%
“…Wherever feasible, use of the Lund University Cardiopulmonary Assist System (LUCAS) device, a mechanical device that provides automatic chest compressions should be encouraged. Institutions should establish policies to address goals of care discussion with patients to help guide providers for the appropriateness of resuscitation efforts [33] . In patients with known or high probability of COVID-19, placement of venous-venous extracorporeal membrane oxygenation should be considered in the setting of respiratory failure and inability to oxygenate.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear whether proceeding with mechanical ventilation or resuscitation maneuvers in those patients with low functional reserve would provide greater survival probability. In relation to cardiopulmonary resuscitation (CPR), previous experiences showed that less than 5 % of Covid-19 patients survived CPR after a cardiac arrest event [ 23 , 24 ]. Regarding mechanical ventilation, in the present study, two-thirds of the non-DNR/DNI (full-code) patients who required intubation recovered from respiratory insufficiency and were able to obtain a successful extubation.…”
Section: Discussionmentioning
confidence: 99%